2022
DOI: 10.1159/000525882
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Bevacizumab in Pretreated Metastatic Breast Cancer: A Systematic Review and Meta-Analysis

Abstract: <b><i>Background:</i></b> The use of bevacizumab in patients with previously treated metastatic breast cancer (MBC) is controversial. This meta-analysis was carried out to evaluate the efficacy and safety of the regimen including bevacizumab among patients with pretreated MBC. <b><i>Methods:</i></b> We systematically searched PubMed, the Cochrane Library, Web of Science, and Embase databases for randomized controlled trials evaluating bevacizumab combined with ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Moreover, a meta-analysis of the E2100, AVADO and RIBBON-1 studies suggested that bevacizumab combined with chemotherapy as a first-line treatment for mBC significantly improved the ORR and PFS time, but did not improve OS time in patients with increased grade 3-4 adverse effects (20). However, the results of another meta-analysis suggested that use of chemotherapy with bevacizumab as an adjuvant, considering its favorable effects on clinical outcomes, was a preferred therapeutic option for patients with MBC, for whom the disease must be rapidly treated (21). Apatinib, a anti-angiogenic TKI with moderate adverse events, can suppress angiogenesis, tumor growth and metastasis by inhibiting the phosphorylation of VEGFR2 and blocking downstream signaling pathways (22).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a meta-analysis of the E2100, AVADO and RIBBON-1 studies suggested that bevacizumab combined with chemotherapy as a first-line treatment for mBC significantly improved the ORR and PFS time, but did not improve OS time in patients with increased grade 3-4 adverse effects (20). However, the results of another meta-analysis suggested that use of chemotherapy with bevacizumab as an adjuvant, considering its favorable effects on clinical outcomes, was a preferred therapeutic option for patients with MBC, for whom the disease must be rapidly treated (21). Apatinib, a anti-angiogenic TKI with moderate adverse events, can suppress angiogenesis, tumor growth and metastasis by inhibiting the phosphorylation of VEGFR2 and blocking downstream signaling pathways (22).…”
Section: Discussionmentioning
confidence: 99%
“…The novel antiangiogenic drug bevacizumab, which is an intravenously administered recombinant monoclonal antibody was developed with VEGF in mind ( 17 ). In clinical practice, bevacizumab has exhibited impressive efficacy alongside manageable safety profiles in heavily treated patients with metastatic breast cancer ( 18 ).…”
Section: Introductionmentioning
confidence: 99%